MORFOLOGI, KARAKTER DAN NERACA KARBON TANAH SAWAH PADA PENGELOLAAN SECARA ORGANIK DAN KONVENSIONAL DI SAWANGAN, MAGELANG - , Erwin Prastowo; , Dr. Ir. Benito Heru Purwanto, M. P., M.Agr. Sc ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Paddy soils possesses morphology and characters widely varied from soil to soil according to soil type and management factors. Rice system should not only issues with high yields achieving but it must governs the control of carbon (C) flows as well. Research performed on organically and conventionally managed rice farming was aimed to evaluate soil morphology, characters, C balance